Autism Spectrum Disorder and the Gut Microbiota : a Systematic Review - Korteniemi, Jenni (My University, 2022)
Autism spectrum disorders (ASD) are a varying group of disorders characterized by deficiency in social interaction and restrictive patterns of behavior and interests. While there are a number of studies focusing on the neuropsychiatric pathogenesis of ASD, its etiology remains unclear. The role of gut-brain-axis in ASD has been studied increasingly and a connection between symptoms and the composition of gut microbiota has been documented in various works. Despite this, the significance of individual microbes and their function is still widely unknown. This work aims to elucidate the current knowledge of the connection between ASD and the gut microbiota in children based on scientific evidence. This is a systematic review done by a literature search from PubMed database focusing on the main findings concerning the gut microbiota composition, interventions targeting the gut microbiota, and possible mechanisms explaining the results in children aged between 2 and 18 years of age. 31 articles that met the selection criteria were included in this systematic review. Most studies in this review found significant differences when comparing the microbial communities of ASD children to healthy controls, while there was notable variation in results when looking at diversity indices or taxonomic level abundance. It seems that there are certain microbial taxa, such as Proteobacteria and Sutterella, and functional markers, such as lower levels of butyrate, that are characteristic for ASD. More research is needed to discover whether some of these features could be used as potential biomarkers for ASD and how the gut microbiota could be targeted in therapeutical interventions.
Keywords: autisminkirjon häiriöt, suolistomikrobisto